Fabrication of Coral‐Shaped MoS2@Ni(Mn)VOX Electrocatalyst for Efficient Alkaline Hydrogen Evolution. Issue 4 (28th January 2022) - Zhang, Bingqian; Li, Yanan; Yi, Jiaxin; Zhang, Yi; Li, Xuchun; Cong, Yanqing
Abstract : Electrochemical hydrogen production is considered as one of the most significant ways to develop clean energy in the future. Herein, the self‐supporting electrocatalyst of MoS2 @Ni(Mn)VO X is fabricated on 3D nickel foam (NF) by a facile two‐step electrodeposition approach. The optimal MoS2 @Ni(Mn)VO X electrode shows an ultralow overpotential of 61 mV to achieve a current density of 10 mA cm −2 and a Tafel slope of 35.1 mV dec −1 in 1 m KOH, which is superior to NF, MoS2 @NF, NiVO X, Ni(Mn)VO X, or MoS2 @NiVO X . The uniformly dispersed coral‐shaped heterostructure exposes more active sites and makes the charge transfer rate faster. The outstanding synergistic effect of MoS2 and transition metal oxides of Ni, Mn, and V also contribute to the enhanced activity of the catalyst. Benefiting from these, MoS2 @Ni(Mn)VO X shows superior alkaline hydrogen evolution reaction activity and long‐term stability. Herein, a novel catalyst for highly efficient hydrogen evolution in alkaline media is provided. Abstract : MoS2 @Ni(Mn)VO X is successfully synthesized using a two‐step electrodeposition method. Benefiting from a rapid charge transfer rate, abundant active sites, and a large effective surface area, it shows excellent activity and maintains prominent durability for 20 h. Herein, a novel catalyst and a new view for the design of multimetal cooperative electrocatalysts for highly efficient hydrogen evolution reactions in alkaline media are provided.